The Adventures of Tom Sawyer - Twain, Mark, 1835-1910 (London Collins Classics, 2011)
HarperCollins is proud to present its new range of best-loved, essential classics
Keywords: Missouri -- Missouri -- Sawyer, Tom (Fictitious character)